Gender and Religion in American Culture, 1870-1930 - Hackett, David G. (Religion and American culture, 1995)
Since the early 1980's, advances in the study of gender in American history have come primarily through an unmasking of the assumptions of earlier studies. Some have questioned the explanatory power of the field's dominant interpretive paradigm, that of “women's sphere,” because this theoretical lens has often led historians to mistake what was said by and about women for their actual historical experience. Others have laid bare the earlier scholarship's assumption of universal gender definitions that do not take into account differences in women's roles based on race, class, or region. Additionally, several historians have begun to explore the influence of gender relations on the lives of men. As a result, we are beginning to get a picture of gender in American history that goes beyond the “women's sphere” experience of white, middle-class, northeastern women.